2022
DOI: 10.52567/pjsr.v4i03.743
|View full text |Cite
|
Sign up to set email alerts
|

TRANSLATION AND VALIDATION OF GENDER MINORITY STRESS & RESILIENCE SCALE

Abstract: The purpose of the present study was to translate Gender Minority Stress & Resilience Scale (GMSR; Testa, 2014) into Urdu language for construct validity of the scale for gender nonconforming individuals living in Pakistani culture. This purpose was accomplished in two phases. In the first phase, the GMSR Scale was translated in to Urdu language by following the steps of back translation method suggested by Brislin (1972).To establish the construct validity of GMSR Scale, data was collected in two phases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In this study, the value of Cronbach’s alpha coefficient was acceptable for evaluating the internal consistency in the interval, other psychometric properties studies (stated in Table 5 ) also reported the acceptable value of this index ( 14 , 28 , 32 ). Cronbach’s alpha coefficient was reported as 0.89 in the original study of this scale, which is slightly lower than the alpha calculated in the present study ( 6 ).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…In this study, the value of Cronbach’s alpha coefficient was acceptable for evaluating the internal consistency in the interval, other psychometric properties studies (stated in Table 5 ) also reported the acceptable value of this index ( 14 , 28 , 32 ). Cronbach’s alpha coefficient was reported as 0.89 in the original study of this scale, which is slightly lower than the alpha calculated in the present study ( 6 ).…”
Section: Discussionsupporting
confidence: 61%
“…In the current study, 30 transgender people answered an 8-item IT scale again with an interval of two weeks, and by comparing the two response stages, the test-retest reliability was calculated through ICC, which showed a favorable value. The test-retest reliability is not mentioned in other psychometric studies ( 6 , 16 , 28 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations